Disruptive Information and the Cost of Equity Finance of Small Firms : Moderating of CEO Succession Mechanism - Kandil, Tarek; Taramol, K. G.; Bhavani, Ganga (Prabandhan: Indian Journal of Management, 2018)
The present paper examined the implementation of radio frequency identification (RFID) as a new platform for developing dynamic capabilities and competencies that enable family businesses to assimilate and respond to unprecedented changes and to reduce the cost of capital finance. In family businesses, the implementation of innovative and advanced technology may be perceived negatively by some entrepreneurs. There is insufficient empirical evidence to support a full understanding of the impact of disruptive information technology on the family firm’s financing costs and the related risk. Understanding of the disruptive innovation effects has valuable implications during the family firms’ succession. The paper tested a sample of 146 listed family businesses in the London Stock Exchange that adopted RFID innovative technology. The findings showed that the UK family firms, which employed the disruptive innovation technology, achieved a better financial performance through enhanced share returns in the short term as well as in the long term. Besides, the listed family firms in the service industry achieved a significant reduction in the equity cost of capital in the long term. During the CEO succession period, the investor of family businesses recognized the benefits of adopting RFID on their supply chain operations.